Students' perceptions of blackboard and moodle in a portuguese university - Carvalho, Ana (2011)
The use of learning management systems (LMS) has grown considerably in universities around the world. The University of Minho (UM) has pioneered in this area in Portugal, adopting Blackboard as its official LMS. Moodle is also used in UM in scattered initiatives, allowing for interesting comparisons. Previous studies comparing Blackboard and Moodle have been confined to limited samples and focused on students’ perceptions only. In this paper, we also try to relate those perceptions to the impact of the LMSs on student level of engagement. We assess the extent and depth of use of the two LMSs, presenting the results of a study of students’ perceptions and experience with both Blackboard and Moodle. Unlike pre- vious studies, more students (46.5%) stated a preference for Blackboard over Moodle, while 34.7% preferred Moodle, and nearly 20% had no preference. Factors that might explain these results are explored in some detail. By and large, a basic utilisation is made of both platforms, as little more than electronic document repositories, in what Francis and Raftery, in 2005, designate as a Mode 1 level of engagement. We could, however, detect some instances of a more sophisticated Mode 2 utilisation, particularly with Moodle, underlining the role of faculty in integrating a sophisticated use of LMSs when designing their courses.